Risk of work-related musculoskeletal disorders and occupational health hazards among the footwear making workers of unorganized sector in West Bengal, India - Biswas, Gourab; Biswas, Dipanjan (International Journal of Occupational Safety and Health, 2026)
Introduction: The shoe-making industry is one of the largest industries in the country. It employs more than 1.10 million workers from rural areas with a lower socio-economic background. These workers are exposed to different types of occupational hazards at the workplace. Musculoskeletal disorder (MSD) is one of the major burdens among the workers. Methods: This study used standard methods and surveys to measure the physiological and demographic characteristics of the shoe-making workers and schoolteachers. Modified Nordic questionnaires and the body part discomfort (BPD) scale were used to record the musculoskeletal disorders and the degree of pain felt. The Rapid Entire Body Assessment (REBA) method was used to evaluate the workers’ working posture. Standard statistical tools were used to analyze the data. Results - In this study, it was found that shoe-making workers were suffering from excess fatigue (88.6%), accidents (92.0%), addiction (78.6%), and MSDs (96.6%). It was observed that the wrist (OR-21.98, 95% CI- 10.06-48.04, p <0.0001) was the most affected body part, followed by the neck, hip, lower back, etc., due to pulling, bending, and twisting postures as well as repetitive actions. Significant correlation had been found between MSD with age and experience. BPD score proportionally increased with age and experience, whereas it was inversely proportional to education and duration of tiffin break. Conclusion: Shoe-making workers suffer from occupational stress and adverse working conditions. Proper working postures, a work-rest cycle, training, education, and frequent medical check-ups can reduce their occupational stress.